2022
DOI: 10.3389/fphar.2022.922232
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol: A potential therapeutic natural polyphenol for neurodegenerative diseases associated with mitochondrial dysfunction

Abstract: Most polyphenols can cross blood-brain barrier, therefore, they are widely utilized in the treatment of various neurodegenerative diseases (ND). Resveratrol, a natural polyphenol contained in blueberry, grapes, mulberry, etc., is well documented to exhibit potent neuroprotective activity against different ND by mitochondria modulation approach. Mitochondrial function impairment is the most common etiology and pathological process in various neurodegenerative disorders, viz. Alzheimer’s disease, Parkinson’s dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 251 publications
1
27
0
Order By: Relevance
“…Thus, it can be concluded that the induced inflammation was associated with DM oxidative stress in the testicular tissue. RSV is a bioactive antioxidant polyphenol and its potency to combat oxidative stress has been documented [19][20][21][22]. We confirm in this study of the antioxidant prowess of RSV in that it significantly elevated the SOD, CAT, and GPx activities in comparison to DM group rats.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Thus, it can be concluded that the induced inflammation was associated with DM oxidative stress in the testicular tissue. RSV is a bioactive antioxidant polyphenol and its potency to combat oxidative stress has been documented [19][20][21][22]. We confirm in this study of the antioxidant prowess of RSV in that it significantly elevated the SOD, CAT, and GPx activities in comparison to DM group rats.…”
Section: Discussionsupporting
confidence: 80%
“…Reproductive damage is a debilitating complication of DM. Resveratrol is a natural polyphenol associated with health-promoting effects in both animals and humans [22]. In the present study, we have reported the effect of RSV on DM-induced testicular damage and endocrine dysfunction.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Among those, the direct non-enzymatic antioxidant ability of Res has been hailed as responsible for the neuroprotective effects of this stilbene. Moreover, Res has been reported to increase the activity of SIRT1, acting as a protective molecule against mitochondrial dysfunctions [ 11 , 39 , 40 , 41 ]. Finally, the interaction of Res with estrogen receptors has also been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Here we hypothesize that ERβ selective ligands, which overcome ERα activation, could increase NGB levels maintaining their protective effects against oxidative stress-induced apoptosis. Two different molecules have been taken into consideration: the diarylpropionitrile (DPN), a synthetic and specific ERβ ligand, and resveratrol (3,5,4′-trans-trihydroxystilbene) (Res), a stilbene family member further identified as a phytoalexin, present in plants such as grape skin, cocoa, various berries and peanuts [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%